A Haven for Suffering: Second Experiential Cooperative Research Study on the Foundations of Counselling and Psychotherapy - Ratté, Jimmy; Dubois, Alain; Caouette, Louise; Roussin, Céline; Goyer, Liette (Canadian Journal of Counselling and Psychotherapy, 2016)
This second study follows up an article published in CJCP in January 2008. Based on Experiential Cooperative Research design (Heron & Reason, 2006), it further explores the fundamentals of the helping relationship in counselling and psychotherapy, in particular a dimension perceived as spiritual or an awareness of the essence of existence. In order to better understand how a spiritual dimension can help create openness to the depths of being, the co-researchers of this reflexive framework study invited four spiritual researchers to share their individual viewpoints on spirituality. The group process and what emerged as essential from these encounters are summarized. The subject-researchers then define, describe, and substantiate seven new counselling foundations that add to those identified in the first study. A critical overview and a creative representation of their findings (Heron, in Reason, 1994) conclude the article.